Special Issue “Superhydrophobic and Icephobic Coatings as Passive Ice Protection Systems for Aeronautical Applications” - Filomena Piscitelli (Applied Sciences, 2024)
The formation of ice can be very dangerous to flight safety, especially in cold climates, since ice accumulated on the surfaces of the aircraft can alter the aerodynamics, increase the weight, and reduce lift, leading to catastrophic stall situations in some cases [...]